Spontaneous intracranial hypotension: a case series and literature review - Pistacchi, Michele; Pezzato, Andrea; Rudà, Roberta; Gioulis, Manuela; Contin, Franco; Fragiacomo, Federica; Marsala, Sandro Zambito (Folia Neuropathologica, 2023)
Spontaneous intracranial hypotension (SIH) is a condition of negative intracranial pressure resulting from cerebrospinal fluid (CSF) leakage from the dural sac and is a well-known cause of orthostatic headache. Diagnosis and management can be difficult, often requiring coordination between multiple disciplines. Low CSF pressure and diffuse meningeal enhancement on brain MRI are the major instrumental features of the classic syndrome. Neuroimaging plays a key role in diagnosing SIH, particularly in atypical clinical presentations, by recognizing the specific findings of brain sagging on MRI and detecting the level of CSF leak on spinal imaging, thus guiding therapy accordingly. Since SIH could present with such a heterogeneous clinical picture, careful history taking and increased awareness of atypical presentations are of utmost importance. We review the existing SIH literature, illustrate management, clinical and neuroimaging findings of four consecutive patients with atypical SIH, who were recently referred to our hospital for evaluation to simplify and streamline the management of SIH.